1995
DOI: 10.1002/jemt.1070300508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SEM processing methods for cultured human lens epithelial cells grown on flat and microcarrier bead substrates

Abstract: The increasing importance of in vitro models has presented new challenges in SEM processing techniques. The present study has evaluated the quality of preservation of cultured human lens epithelial cells processed by critical point, Peldri II, and tert-butyl alcohol drying. Specimens processed by critical point drying produced specimens with severe cracking of cell processes and microcracks across cell membrane surfaces. Peldri II and tert-butyl alcohol drying eliminated breakage of the filopodia and lamellipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although some cells contain cracks, we believe this is related to imperfect fixation and critical point drying (CPD). 51 Importantly, the SEM images confirm that the cells generally do not show unexpectedly abnormal morphologies and seem to adhere closely to the substrate. 52 Moreover, phase contrast micrographs of the cultured cells also did not show any abnormalities (Figure 2d,e).…”
Section: ■ Results and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although some cells contain cracks, we believe this is related to imperfect fixation and critical point drying (CPD). 51 Importantly, the SEM images confirm that the cells generally do not show unexpectedly abnormal morphologies and seem to adhere closely to the substrate. 52 Moreover, phase contrast micrographs of the cultured cells also did not show any abnormalities (Figure 2d,e).…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…To characterize cellular growth and adhesion to the nanostructured gold, we used SEM imaging (Figure e,f). Although some cells contain cracks, we believe this is related to imperfect fixation and critical point drying (CPD) . Importantly, the SEM images confirm that the cells generally do not show unexpectedly abnormal morphologies and seem to adhere closely to the substrate .…”
Section: Resultsmentioning
confidence: 80%
“…Apparently the first to report freeze-drying from t-butanol, Wheeler et al [7], examined canine endocardia and found the freeze-drying to be equivalent to critical-point drying, but more convenient. Cantu-Crouch et al [8] studied human lens epithelial cells and found those that were freeze-dried from t-butanol, compared to those critical-point dried, suffered fewer cracks across membranes and cell processes. Finally, critical-point dried fish sperm shrank to a significantly greater extent than those freeze-dried in t-butanol [9].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Boyde [10] reported extensive shrinkage for a mouse embryo limb dehydrated in t-butanol. Mouse limbs might be particularly prone to shrinkage in t-butanol, but Boyde dehydrated the sample in t-butanol; whereas for freeze-drying, samples are customarily dehydrated in ethanol prior to infiltration with t-butanol [1, 7, 8, 9]. Boyde wrote that he presented the results for t-butanol dehydration at Scanning Electron Microscopy 1978 (Los Angeles, CA) and “in many lectures on specimen preparation” [10].…”
Section: Discussionmentioning
confidence: 99%
“…Storing the cells at temperatures between 12°C and 20°C ensured the best preservation of ultrastructure, although increased intercellular spacing was seen after storage at all temperatures. Some of the intercellular gaps, however, represented microcracks due to critical point drying as part of sample preparation for scanning electron microscopy [35]. Apical microvilli, which have been demonstrated in ARPE-19 previously [31], have been reported to decrease in number in aging RPE cells [36].…”
Section: Discussionmentioning
confidence: 99%